The role of the coach in action sports: Using a problem-based learning approach - Ojala, A.-L.; Thorpe, H. (International Sport Coaching Journal, 2015)
Action sports (e.g., snowboarding, skateboarding, windsurfing, BMX) have traditionally celebrated antiauthoritarian, do-it-yourself and anticompetition cultural values. With the institutionalization and commercialization of action sports over the past two decades, and the introduction of mega-sports events such as the X Games, and the inclusion of some action sports into the Olympic Games (i.e., snowboarding, freestyle skiing, BMX), action sport athletes are increasingly working with coaches, psychologists, agents, managers and personal trainers to improve their performances. In this Insights paper we consider coaching in action sports via the case of Finnish professional snowboarders` attitudes to coaches. Drawing upon conversations with elite freestyle snowboarders we briefly present insights into their perceptions of the various positions of coaches in professional snowboarding before we offer suggestions built upon a Problem-based learning approach for coaches interested in working with action sport athletes.